Risk factors for delay of adjuvant chemotherapy in non-metastatic breast cancer patients: A systematic review and meta-analysis involving 186982 patients - He, Xiaofang; Ye, Fen; Zhao, Bingcheng; Tang, Hailin; Wang, Jin; Xiao, Xiangsheng; Xie, Xiaoming (PLOS ONE, 2017)
Purpose Delay performance of adjuvant chemotherapy (AC) after surgery has been presented to affect survival of breast cancer patients adversely, but the risk factors for delay in initiation remain controversial. Therefore, we conducted this systematic review of the literature and meta-analysis aiming at identifying the risk factors for delay of adjuvant chemotherapy (DAC) in non-metastatic breast cancer patients. Methods The search was performed on PubMed, Embase, Chinese National Knowledge Infrastructure and Wanfang Database from inception up to July 2016. DAC was defined as receiving AC beyond 8-week after surgery. Data were combined and analyzed using random-effects model or fixed-effects model for risk factors considered by at least 3 studies. Heterogeneity was analyzed with meta-regression analysis of year of publication and sample size. Publication bias was studied with Egger’s test. Results A total of 12 observational studies including 186982 non-metastatic breast cancer patients were eligible and 12 risk factors were analyzed. Combined results demonstrated that black race (vs white; OR, 1.18; 95% CI, 1.01–1.39), rural residents (vs urban; OR, 1.60; 95% CI, 1.27–2.03) and receiving mastectomy (vs breast conserving surgery; OR, 1.35; 95% CI, 1.00–1.83) were significantly associated with DAC, while married patients (vs single; OR, 0.58; 95% CI, 0.38–0.89) was less likely to have a delay in initiation. No significant impact from year of publication or sample size on the heterogeneity across studies was found, and no potential publication bias existed among the included studies. Conclusions Risk factors associated with DAC included black race, rural residents, receiving mastectomy and single status. Identifying of these risk factors could further help decisions making in clinical practice.